Integrative Therapy Focused on Trauma for People with Intellectual Disability (TIT-ID): A Therapeutic Answer to Abuse and Intellectual Disability Experience in the Individual and the Family - Núñez-Polo, Mercedes Hernández; Carrasco, Alberto Alemany; Muñoz, Israel Berenguer; Zapata, María Recio; Cafranga, Almudena Martorell (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Persons with Intellectual Disabilities (ID) have ten times more risk of suffering abuse than persons without ID. When somebody is born with ID, his/her story is printed by trauma of ID (primary trauma). If we add the trauma from disability to the trauma from abuse (secondary trauma), we find very vulnerable population with a high probability of being re-victimised. Victim Support Unit for Persons with Intellectual Disability (UAVDI) proposes an Integrative Therapy focused on Trauma for people with ID (TIT-ID). This therapy is focused on trauma, including the victim and their families and professionals, through different approaches. It intervenes from individual pathoplasty, taking into account side effects caused by abuse. It also works from a systemic perspective of the primary trauma due to ID and primary grief in the individual and his family. It includes a person-centre intervention with attachment theory and organised through phases from theory of structural dissociation. It is very important to do a rigorous analysis of variables involved in the impact of grief (primary trauma) and later in the impact of abuse experience (secondary trauma). The goals of therapy will be planned according to the individual diagnosis. The cross-cutting objectives are the establishment of consistent links to enable the person to restore their feelings of security and sense of self-worth, and also the development of a resilient personality.